IMPROVING CHILDREN'S ORAL LANGUAGE CREATIVITY THROUGH THE DRAWING CARD METHOD WITH GAMES PLASTIC BALLS IN GROUP B IN KINDERGARTEN TUT WURI HANDAYANI ACEH BESAR - Cut Fazlil Hanum (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
ABSTRACT One of the components to improve children's learning achievement is the learning media used. Teachers must be able to choose suitable learning media according to the material being taught. One of the media used is picture card media with plastic ball games. The formulation of the problem in this study is How is the implementation of learning in Improving Children's Spoken Language Creativity through the Picture Card Method with Plastic Ball Games in group B at Tut Wuri Handayani Kindergarten, Kuta Malaka District, Aceh Besar Regency and How is the Increase in Children's Spoken Language Creativity through the Picture Card Method with Plastic Ball Games in group B at Tut Wuri Handayani Kindergarten, Kuta Malaka District, Aceh Besar Regency. The purpose of this study was to determine the implementation of learning in improving children's spoken language creativity through the Picture Card Method with Plastic Ball Games in group B at Tut Wuri Handayani Kindergarten, Kuta Malaka District, Aceh Besar Regency and to determine the increase in children's spoken language creativity through the Picture Card Method with Plastic Ball Games in Group B at Tut Wuri Handayani Kindergarten, Kuta Malaka District, Aceh Besar Regency. The research design is in the form of class action research, which is a research that refers to the classroom, The population in this study were group B children at Tut Wuri Handayani Kindergarten, Aceh Besar. The sample in this study were 28 children, consisting of 11 boys and 17 girls. Data collection techniques in this study are observation techniques. Data collection was carried out in one cycle, because there was an increase in children's oral language creativity with the use of picture card media with plastic ball games to increase the oral language creativity of group B children at Tut Wuri Handayani Kindergarten Aceh Besar.